Condition-specific associations of symptoms of depression and anxiety in adolescents and young adults with asthma and food allergy - Ferro, M.; Van Lieshout, R.; Scott, J.; Alati, Rosa; Mamun, A.; Dingle, K. (Informa Healthcare, 2016)
© 2016 Taylor & Francis. Objective: This study examined associations of asthma and food allergy with symptoms of depression and anxiety at 14 and 21 years of age to determine whether condition-specific associations exist. Methods: Data come from 4972 adolescents in the Mater University Study of Pregnancy. Symptoms of depression and anxiety were assessed using the Youth Self-Report and Young Adult Self-Report. Results: Condition-specific associations between asthma and depression, OR = 1.37 [1.12, 1.67] and between food allergy and anxiety, OR = 1.26 [1.04, 1.76] were found during adolescence, but not in young adulthood. Whereas asthma was associated with resolved depression, OR = 1.70 [1.13, 2.55], food allergy was associated with persistent anxiety, OR = 1.26 [1.01, 1.59]. Conclusions: In adolescents, asthma is associated with an increased risk of clinically relevant symptoms of depression and food allergy with an increased risk of clinically relevant symptoms of anxiety. Future research is needed to clarify directionality and mechanisms explaining these relationships. Health professionals should be aware of the increased risk of mental health problems in adolescents with asthma or food allergy.